Augmented Renal Clearance in Patients With Febrile Neutropenia is Associated With Increased Risk for Subtherapeutic Concentrations of Vancomycin. Issue 6 (December 2016) - Hirai, Keita; Ishii, Hidetoshi; Shimoshikiryo, Takayuki; Shimomura, Tatsuki; Tsuji, Daiki; Inoue, Kazuyuki; Kadoiri, Toshihiko; Itoh, Kunihiko
Abstract : Background: Augmented renal clearance (ARC) has frequently been observed in critically ill patients. The risk factors for ARC in patients, including those in the general ward, and their influences on vancomycin (VCM) treatment remain unclear. The aims of this study were to investigate the risk factors for ARC and to evaluate the influence of ARC on the pharmacokinetic parameters of VCM. Methods: This study included a total of 292 patients with VCM treatment who had normal serum creatinine concentrations. ARC was defined by an estimated creatinine clearance ≥130 mL·min −1 ·1.73 m −2 . The risk factors for ARC were determined with stepwise logistic regression analysis. The pharmacokinetic parameters of VCM were estimated through the Bayesian method using a 2-compartment model. Results: ARC was observed in 48 patients (16.4%). Age ⩽65 years [odds ratio (OR): 5.77; 95% CI: 2.89–11.97; P < 0.0001], brain injury (OR: 5.11; 95% CI: 1.49–17.57; P = 0.0086), febrile neutropenia (OR: 2.76; 95% CI: 1.11–6.67; P = 0.0254), and a mean volume of infusion fluid ≥1500 mL/d (OR: 2.53; 95% CI: 1.27–5.16; P = 0.0091) were independent risk factors for the occurrence of ARC. The patients with ARC exhibited higher VCM clearance values than the non-ARC patients. The median trough serum concentrations of VCM were 7.4 (interquartile range: 5.2–11.6) mcg/mL in the ARC patients and 12.2 (8.9–16.3) mcg/mL in the non-ARC patients ( P < 0.0001). Subtherapeutic trough concentrations of VCM (<10.0 mcg/mL) were found in 68.8% of the ARC patients and in 32.8% of the non-ARC patients ( P < 0.0001). Conclusions: This observational study investigated the influence of febrile neutropenia on the emergency of ARC for the first time. ARC was strongly associated with VCM pharmacokinetics, and two-thirds of the ARC patients had subtherapeutic VCM concentrations. In patients with ARC, individualized dosing regimens are required to achieve the target trough concentration.